PENGARUH PAPARAN GAS KLORIN DAN TEKANAN DARAH TERHADAP KEJADIAN GANGGUAN PENGHIDU PADA PEKERJA PABRIK TEKSTIL - , WINDA ROSITA SEPTANTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Chlorine is a chemical substance used broadly in industry, mostly by paper and textile industries. Chlorine is also an irritative substance to mucous layer, especially to the respiratory tract. While hypertension worsens the effect of this irritant. Hypertension is known to affect the peripheral blood vessels, causing peripheral neuropathy. These two conditions can alter the function of olfactory organ. Objectives: to understand the effect of high blood pressure and chlorine exposure to the olfactory dysfunction event in textile workers. Method: This is a cross-sectional study, using chi-square test as the analytic test. Subject collection was done through the anamnesis, anterior and posterior rhinoscopy. Eighty textile workers in âXâ textile industry who have already fulfilled the inclusion and exclusion criterias, their olfaction were checked using the odor stick test. Result: In the exposed group, there were 10 people out of 40 (12,5% of the subjects) have olfactory dysfunction. While in the unexposed group there were 2 people out of 40 (2,5% of the subjects) haveolfactory dysfunction, with PR=5 and p-value = 0,012. In hypertension group, 6 out of 10 people (7,5% of the subjects) were found having olfactory dysfunction. While in non-hypertension group, 6 out of 64 people (7,5% of the subjects) were found having olfactory dysfunction with PR = 6,97 and p-value = 0,083 (95% CI, PR>5, p-value â¤0,05). Conclusion: Chlorine exposure is a risk factor and significantly affecting the olfactory dysfunction. While hypertension is not significantly affecting the olfactory dysfunction.